Feedback Regulation and Time Hierarchy of Oxidative Phosphorylation in Cardiac Mitochondria - Vinnakota, Kalyan C. (Biophys J, 2016)
To determine how oxidative ATP synthesis is regulated in the heart, the responses of cardiac mitochondria oxidizing pyruvate to alterations in [ATP], [ADP], and inorganic phosphate ([P(i)]) were characterized over a range of steady-state levels of extramitochondrial [ATP], [ADP], and [P(i)]. Evolution of the steady states of the measured variables with the flux of respiration shows that: (1) a higher phosphorylation potential is achieved by mitochondria at higher [P(i)] for a given flux of respiration; (2) the time hierarchy of oxidative phosphorylation is given by phosphorylation subsystem, electron transport chain, and substrate dehydrogenation subsystems listed in increasing order of their response times; (3) the matrix ATP hydrolysis mass action ratio [ADP] × [P(i)]/[ATP] provides feedback to the substrate dehydrogenation flux over the entire range of respiratory flux examined in this study; and finally, (4) contrary to previous models of regulation of oxidative phosphorylation, [P(i)] does not modulate the activity of complex III.